Devastating Insomnia Experience Following General Anaesthesia for Mastoidectomy Surgery - Misrona, LH; Misron, SNF; Misron, K (IIUM Medical Journal Malaysia, 2020)
Sleep disorder including insomnia is one of the complications of general anaesthesia. It is not uncommon and it is temporary but majority remains unnoticed and untreated. The effect of insomnia ranges from mild to severe, influencing both physical and mental health. Surgeon and anaesthetist need to identify this complication so that an appropriate treatment can be delivered. In complicated case, psychiatrist involvement is crucial. The treatment is symptomatic and temporary. We reported a case of distressful sleep disorder as a sequelae of general anaesthesia for mastoidectomy surgery. Subsequently after symptomatic treatment, he recovered completely and regained his normal sleep pattern.